Pengembangan Model Pembelajaran Berbasis Sistem Informasi Budaya Nusantara untuk Referensi Kontekstual Portofolio Karya Seni Mahasiswa PPG yang Terstandarisasi dengan Industri Kreatif - Hartono, Hartono; Fajarianto, Otto; Prasetyo, Abdul Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Strengthening the relevance of art education in the Teacher Professional Education Program (PPG) requires integration between local culture and the needs of the creative industry. This research aims to develop a learning model based on the Nusantara Cultural Information System that functions as a contextual reference in the preparation of a portfolio of PPG students' artworks. This model is designed so that students' portfolios not only reflect artistic competence, but also conform to creative industry standards based on local cultural richness. The approach used is Research and Development with the ADDIE model, focused on the Analysis, Design, and Development stage. At the analysis stage, a needs study was carried out through literature studies, curriculum analysis, and interviews with stakeholders in the creative industry and art education. The design stage produces a digital-based learning framework with the integration of Nusantara cultural content and creative production references. At the development stage, a prototype model is prepared in the form of learning modules, digital information systems, and guidelines for the preparation of contextual portfolios. The results of the initial formative evaluation show that this model has the potential to improve the contextuality of the work, encourage the exploration of local culture, and strengthen the linkage between arts education and the needs of the creative industry. This research contributes to the development of a PPG curriculum that is more relevant and adaptive to the development of the digital arts and culture ecosystem.